An Investigation into the Fundamental Principles of the Yoga Sūtra of Patañjali (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Yoga Sutra of Patajali is a sacred philosophical work that offers instruction on how toachieve enlightenment and self-realization via the discipline of yoga, and this study dives into itsfoundational ideas. The Yoga Sutra, written by the sage Patajali over a thousand years ago, provides ashort and thorough overview of yoga's tenets, techniques, and levels. The study delves at the applicationof the Yoga Sutra and its continued relevance in today's world. It explores how to apply the Yoga Sutrato one's everyday life, the significance of self-care and wellness, and the ways for achieving mentalclarity and tranquilly. Samadhi, a meditative state of oneness and spiritual emancipation, is alsoinvestigated for the ways in which it might alter one's outlook on life and the world.